Cassava (Manihot esculenta) Slow Anion Channel (MeSLAH4) Gene Overexpression Enhances Nitrogen Assimilation, Growth, and Yield in Rice - Song, Linhu; Wang, Xingmei; Zou, Liangping; Prodhan, Zakaria; Yang, Jiaheng; Yang, Jianping; Ji, Li; Li, Guanhui; Zhang, Runcong; Wang, Changyu; Li, Shi; Zhang, Yan; et al. (Frontiers in Plant Science, 2022)
Nitrogen is one of the most important nutrient elements required for plant growth and development, which is also immensely related to the efficient use of nitrogen by crop plants. Therefore, plants evolved sophisticated mechanisms and anion channels to extract inorganic nitrogen (nitrate) from the soil or nutrient solutions, assimilate, and recycle the organic nitrogen. Hence, developing crop plants with a greater capability of using nitrogen efficiently is the fundamental research objective for attaining better agricultural productivity and environmental sustainability. In this context, an in-depth investigation has been conducted into the cassava slow type anion channels (SLAHs) gene family, including genome-wide expression analysis, phylogenetic relationships with other related organisms, chromosome localization, and functional analysis. A potential and nitrogen-responsive gene of cassava (MeSLAH4) was identified and selected for overexpression (OE) analysis in rice, which increased the grain yield and root growth related performance. The morpho-physiological response of OE lines was better under low nitrogen (0.01 mM NH4NO3) conditions compared to the wild-type (WT) and OE lines under normal nitrogen (0.5 mM NH4NO3) conditions. The relative expression of the MeSLAH4 gene was higher (about 80-fold) in the OE line than in the wild-type. The accumulation and flux assay showed higher accumulation of NO3- and more expansion of root cells and grain dimension of OE lines compared to the wild type plants. The results of this experiment demonstrated that the MeSLAH4 gene may play a vital role in enhancing the efficient use of nitrogen in rice, which could be utilized for high-yielding crop production.